Multiple Sclerosis: LIFNano-CD4 for Trojan Horse Delivery of the Neuro-Protective Biologic “LIF” Into the Brain: Preclinical Proof of Concept - Flor, Raul de la; Robertson, Janette; Shevchenko, Rostislav V.; Alavijeh, Mo; Bickerton, Sean; Fahmy, Tarek; Metcalfe, Su M. (Frontiers in Medical Technology, 2021)
Multiple Sclerosis (MS) is a demyelinating autoimmune disease that attacks the brain, with year-on-year loss of brain volume, starting late teens and becoming manifest late twenties. There is no cure and current therapies are immunosuppressive only. LIF is a vital stem cell growth factor active throughout life - and essential for health of the central nervous system (CNS), being tolerogenic, myelinogenic, and neuroprotective. Nano-formulation of LIF (LIFNano) using FDA-approved PLGA captures LIF's compound therapeutic properties, increasing potency one thousand-fold when targeted to CD4 (LIFNano-CD4). Moreover, circulating CD4+ lymphocytes are themselves regulated by LIF to express the Treg phenotype, known to release T cell-derived LIF upon engagement with cognate antigen, perpetuating antigen-specific self-tolerance. With the longer term aim of treating inflammatory lesions of MS, we asked do LIFNano-CD4 cross the blood-brain barrier (BBB) ? We measure pK and pD using novel methodologies; demonstrate crossing of the BBB; show LIF-cargo-specific anti-inflammatory efficacy in the frontal cortex of the brain; and show safety of intravenous delivery of LIFNano-CD4 at doses known to provide efficaceous concentrations of LIF cargo behind the BBB.